Mexico : Institutional Coordination for Regional Sustainable Development - World Bank (Washington, DC, 2013)
This report analyzes, through a review of the regulatory framework, case studies, and international experiences, current arrangements for coordination of government programs in priority regions in Mexico, as well as opportunities for better addressing the development needs of those regions via enhanced coordination. The broad hypotheses underpinning the analysis are: 1) Poor coordination (within government and between government and civil society) impedes the effective use of government resources (and the mobilization of private ones) in backward regions. 2) Participatory planning fora at the regional (i.e., inter-municipal) level may provide an institutional and operational framework through which those impediments can be removed. The report is organized as follows: Chapter 2 reviews the recent evolution of regional development policies. Chapter 3 develops a conceptual framework for analyzing horizontal and coordination problems as they relate to regional policies. Chapter 4 discusses the normative framework for coordination developed in Mexico's laws and regulations. Chapter 5 analyzes current challenges to, and opportunities for, effective coordination in Mexico on the basis of four case studies. Chapter 6 discusses international experiences with horizontal and vertical coordination in several Latin American countries, as well as the relevance and applicability of those lessons to Mexico. Finally, chapter 7 develops tentative recommendations.